Peningkatan Penjualan Produk Merica dan Cengkeh Melalui Strategi Media Pemasaran Secara Online - Asdar Djamereng; Lilis Nur Hayati; Andi Syifa Salsabila Ruflin; Luthfiya Salsabila Fakhruddin (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Online sales have become one of the main factors supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study explores a Community Service (PkM) program in Benteng Gantarang Village aimed at increasing sales of MACEH (Pepper & Clove) products through online marketing media strategies. The program implementation steps, including an initial survey and analysis focused on understanding market needs and consumer preferences became the basis in the development of MACEH products. Production socialization involved specialized training to improve the technical skills of MSME players in the creation and packaging of efficient and attractive products and the exposure of the MACEH website. System implementation included the construction and setup of a website designed to facilitate online transactions and expand the market reach of MACEH products through digital marketing. Program outcomes include increased production, changes in product packaging, increased income, and expanded online marketing through the website. his study reflects the positive impact of the PkM program on MACEH MSMEs and the potential for increased sales of MACEH products through online marketing media strategies that effectively expand the market and attract new consumers.